Luminescent nanohybrids based on silica and d-f heterobimetallic silylated complexes: new tools for biological media analysis - Sábio, Rafael Miguel [UNESP] (2016)
The design of heterobimetallic luminescent complexes has gained growing interest in recent years due to their unique photophysical properties. More specifically, the development of heterobimetallic complexes using d-block chromophores to sensitize the near-infrared (NIR) emission of lanthanide complexes (such as Nd(III) and Yb(III)) has received significant attention taking into account their longer emission wavelengths and the interest of the NIR emission which penetrates human tissue more effectively than UV light. These properties give them potential applications in medical diagnostics or biomedical assays. Transitions to excited state levels of transition metal complexes occurring in the visible and characterized by large absorption coefficients, could efficiently sensitize f-f levels of Ln(III) ions. In this work new d-f heterobimetallic complexes containing silylated ligands were prepared supported on silica materials. [Ru(bpy)2(bpmd)]Cl2 (labeled Ru), [Ru(bpy)(bpy-Si)(bpmd)]Cl2 (labeled RuL) and [Ln(TTA-Si)3] (labeled LnL3) and d-f heterobimetallic complexes, Ru—LnL3 and Ln—RuL (Ln = Nd3+, Yb3+) were prepared. Structural characterization was carried out by Raman Scattering, 1H and 13C NMR spectroscopies. Results obtained from 1H-13C HMBC and HSQC correlation NMR spectra confirm the formation of proposed complexes. Photophysical properties studies highlight the efficiency of Ru—Ln energy transfer processes in NIR-emitting lanthanide complexes mediated by conjugated bridging ligand (2,2'-bipyrimidine). Lifetime measurements were carried out and values of quantum yield for energy transfer (ET) between 30 and 84 % could be evaluated. ET of 73.4 % obtained for the Yb—RuL complex is the largest value reported for Ru(II)—Yb(III) heterobimetallic complexes so far. Grafting on different silica matrix was also demonstrated. SiO2-Ru, SiO2-NdL3 and SiO2-YbL3 nanohybrids were obtained with grafting efficiencies from 0.08 to 0.18 mmol g-1 of silica. SiO2-RuNd and SiO2-RuYb were performed from simultaneous grafting of ruthenium and lanthanides silylated complexes. Grafting efficiencies from 0.10 to 0.16 were obtained. ET of 40 and 27.5 % were obtained from SiO2-RuNd and SiO2-RuYb, respectively. The higher values observed for the Nd(III) nanohybrid is well explained by the matching of donor and acceptor energy levels. SiO2-RuYbL3, SiO2-YbRuL, SiO2 d-YbRuL and SiO2-NdRuL were carried out from grafting of d-f heterobimetallic silylated complexes. Grafting efficiencies from 0.03 to 0.17 were obtained. Luminescent properties from these nanohybrids were similar to the free complexes. However the SiO2-YbRuL and SiO2 d-YbRuL showed distinct luminescent profiles compared with the free Yb—RuL. The grafting inside the mesoporous channels may prevent luminescent desactivation processes comparing to the dense silica matrix. The photophysical properties associated with the morphology and stability of the mesoporous silica matrix allow suggesting these new NIR luminescent nanohybrids as nanoprobes or nanomarkers in biomedicine.